UPAYA PEMBINAAN AKHLAK ANAK DI KALANGAN USTADZ/USTADZAH PONDOK PESANTREN DARUL ILMI BANJARBARU - Ira Septiarini; Siti Rahmawati (STAI AL FALAH Banjarbaru, 2020)
This research discusses the efforts to foster children's morality among ustadz / ustadzah Pondok Pesantren Darul Ilmi Banjarbaru. The formulation of this research problem is how the efforts to foster children's morality among ustadz / ustadzah Pondok Pesantren Darul Ilmi Banjarbaru and what are the factors that affect it. The subject in this study was ustadz / ustadzah who taught at Pondok Pesantren Darul Ilmi Banjarbaru and had 8 children. While the object in this study is the efforts to foster children's morality among ustadz / ustadzah in Pondok Pesantren Darul Ilmi Banjarbaru and the factors that affect it. The data collection techniques used in this study are observation, interview and documentation. Based on the research, it is known that the efforts to foster children's morality among ustadz / ustadzah Pondok Pesantren Darul Ilmi Banjarbaru has been running well. This can be seen from the efforts of parents in providing examples of conscientiousness, giving advice, rewarding and punishment and providing supervision. While the factors that affect the conducive environment and children are placed by their parents in Islamic schools. Keywords: Efforts to Foster Morality, Children, Boarding Schools